ANALISIS POLA DAN TREN METODOLOGI PENELITIAN PADA SKRIPSI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING - Muhammad Iqbal; Agus Jayadi; Nuraeni; Sunandar Apriawan Mulyanto (Realita : Jurnal Bimbingan dan Konseling, 2026)
Undergraduate thesis represents a final academic work that reflects students’ research literacy and methodological competence after completing their coursework. This study aimed to analyze patterns and trends of research methodology in undergraduate theses of the Guidance and Counseling Study Program, encompassing research approaches and types, variable patterns, data collection and analysis techniques, temporal trends, and methodological component consistency. This descriptive study with document analysis approach analyzed 124 theses completed between 2020–2023. Data were collected using extraction sheets and analyzed with descriptive statistics and trend analysis. Results showed that all theses (100%) used quantitative approach, with pre-experimental/quasi-experimental designs (62.1%) being dominant. Thematic categorization of variables revealed dominance of counseling services and techniques (62.90%), followed by individual psychological aspects (12.90%). Trends indicated an increase in pre-experimental proportion from 42.6% (2020) to 85.7% (2023). Questionnaires were the primary data collection technique (88.7%), with t-test (76.6%) as the dominant analysis method. The consistency level between research problems and research types reached 98.4%, while consistency between research types and data analysis methods reached 96.8%. These findings indicate good methodological consistency with research orientation toward micro-intervention practices, while also suggesting potential for developing research approach diversity and contextual factor exploration to enrich students’ academic perspectives.